COMMUNITY EMPOWERMENT THROUGH V-CAKES TRAINING (VEGETABLE CAKES) TO DEVELOP KNOWLEDGE AND ENTREPRENEURIAL ATTITUDES - Dinie Anggraeni Dewi; Dudung Priatna; Yayang Furi Furnamasari; Enceng Suwarna (Pasundan International of Community Services Journal (PICS-J), 2020)
The research objective was to empower the community through training in v cakes (vegetable cakes) to increase the knowledge and entrepreneurial attitudes of the community in Palintang Village, Bandung. The method used is quasi-experimental combined with Systemic, Holistic, Interdisciplinary, and Participatory approaches. The research design used posttest only group design (treatment by subject design). The activities carried out began with problem identification, then prioritized problems, and then an action plan was made. This action plan was used as a research intervention in the form of entrepreneurship training. The independent variable is community empowerment through vegetable cakes. The dependent variables are (a) knowledge of entrepreneurship and (b) entrepreneurial attitudes. The data obtained were analyzed descriptively by looking for the percentage change and followed by a paired t-test with a significance level of 5% to analyze the differences in people's knowledge and attitudes between before and after the training. The results of the data analysis showed that the community's knowledge and attitudes were different between the pre and post-V cakes training (p <0.05). In this case, there was an increase in knowledge by 21.18%, and entrepreneurial attitudes increased by 9.57%. Thus it can be concluded that community empowerment through v-cakes training can improve the knowledge and entrepreneurial attitudes of the community in Palintang village, Bandung.